Studies towards the synthesis of novel, renewable monomers sourced from terpenes - Smith, Sean (2020)
The multitude of commercially available plastics, ubiquitous in modern society, with uses from food contains to surgical tools, is vast. However, the major feedstock for these materials is crude oil, which accounts for 7% of oil consumption worldwide – a figure that is predicted to rise substantially in the near future. To address this problem, a wide range of renewable resources have been identified as potential feedstocks of new, sustainably sourced polymer materials. Terpenes represent one of these potential feedstock options, and are mainly sourced from waste streams of existing industries – most notably paper and citrus juice production. This class of compounds provides an opportunity for the polymer industry to explore novel materials and potentially reduce dependency on non-renewable resources. This report details the studies towards synthesis of potential monomers from terpenes using sustainable organic transformations. Short (3 synthetic steps or less) syntheses, involving reactions utilising high atom economy and/or catalysis, form the main focus of the investigations. Of the successful reactions performed, these protocols have been extensively optimised to provide the best yield and selectivity for the desired products, as well as operational simplicity and sustainable chemical reagents involved in carrying out the transformations themselves. The monomers produced during this work are suitable for a variety of polymerisation techniques, including free radical polymerisation, ring-opening polymerisation and other step-growth methods. The resulting polymers have also shown promise in a variety of applications when tested by collaborators, with particular focuses on vaccine adjuvants and alternating hard and soft tri-block co-polymers for thermoplastic elastomer formation.